Understanding AI Usage in Academics among Vocational High School Students - Nanang Joko Sulistyono; Suparji Suparji; Theodorus Wiyanto; Ratna Suhartini; Ilham Ilham (Westscience Press, 2024)
The purpose of this study is to gauge the degree of knowledge that high school students pursuing vocational training have about using artificial intelligence in the classroom and to pinpoint the variables that impact that knowledge. As artificial intelligence (AI) permeates more and more industrial sectors, it is imperative that vocational high school students understand AI and be prepared for its future. Using a mixed-methods approach, this study included 500 Indonesian students enrolled in vocational high schools who represented a range of academic levels through qualitative interviews and quantitative surveys. The study's conclusions show that students at vocational high schools have differing levels of comprehension about artificial intelligence (AI), with a variety of factors like socioeconomic status, school curriculum, and access to technology playing a major influence. The research's ramifications include suggestions for creating more efficient.